Analysing the Interconnectedness of Cultural Values in Fine Art Works with Roland Barthes' Semiotic Approach - I Gede Anjas Kharisma Nata; Lalu Exel Ardi Alfiansyah; Mohamad Yudisa Putrajip; Qatrunnada, Qatrunnada; Ashar Banyu Lazuardi (Jurnal Multidisiplin Sahombu, 2025)
Cultural values are concepts, beliefs, principles, and standards of behavior shared by a particular society or group. These values reflect the way a community views the world, life, and social interaction, and provide guidance for group members in living their daily lives. The research method used in this research is descriptive qualitative research method. This method is carried out by analyzing, describing, and summarizing various conditions and situations from various data that have been collected from interviews or observations about problems in the field. This research was conducted in several steps to ensure accurate and relevant data. The conclusion that can be drawn from this research is that each work has its own cultural values contained in it, where each work has similarities in reflecting the identity and cultural heritage of the community. These values provide guidance for the community to maintain traditions and understand the meaning of life through the symbols in the artwork. This confirms that artwork is not only an aesthetic expression, but also a medium to convey deep and meaningful cultural messages. Thus, artworks play an important role in preserving and teaching cultural values to future generations.